Association of BsmI and ApaI Polymorphisms of the Vitamin D Receptor Gene with Dyslipidemia in Patients with Coronary Artery Disease. - Sergeeva, E.G; Ionova, Z.I (Journal of Bioinformatics And Diabetes, 2020)
Purpose The goals of the present study were to assess the genotypic and allelic distribution of Bsm-I (rs1544410) and Apa-I (rs7975232) polymorphisms of the vitamin D receptor (VDR) gene in coronary artery disease (CAD) patients in comparison to control patients of the same age without CAD and to determine whether these gene variants are associated with dyslipidemia. Materials and Methods Based on a case-control design, 302 hospitalized patients  with CAD and 194 people of comparable age without CAD were enrolled in the study. The BsmI and ApaI polymorphisms of VDR gene were studied using polymerase chain reaction followed by restriction analysis. The allele digested by the restriction enzyme was denoted by a lower letter, whereas that not digested was indicated by a capital letter. Determination of the level of vitamin D and immunoreactive insulin in the blood serum was carried out using the immuno-enzyme method. Results The bb genotype of Bsm-I VDR gene polymorphism was detected more often in patients with CAD than in the comparison group with an increased risk of CAD by 1.52 times (p=0.006, OR=1.52(1.05÷2.2). The level of HDL cholesterol was higher in CAD patients − carriers of BB genotype compared to its level in Bb genotype carriers and bb genotype carriers (1,13±0,05 mmol/l, 1,01±0,03 mmol/l, 1,02±0,03 mmol/l respectively, p<0,05). The level of vitamin D was higher in patients with BB genotype compared to its level in bb genotype carriers (45.12±3.73 nmol / l and 34.16±1.95 nmol/l respectively, p=0.008). The occurrence of a allele of Apa-I VDR gene polymorphism was higher in patients with CAD than in the control group (p=0.02, OR=1.21(0.93÷1.57). HDL cholesterol level was higher in CAD patients - AA genotype carriers compared with carriers of Aa and aa genotypes (1.18±0.08 mmol / l, 1,02±0.02 mmol / l and 1.01±0.03 mmol/l respectively, p<0,05). Immunoreactive insulin level was significantly higher in CAD patients – aa genotype carriers. No differences in LDL cholesterol and triglycerides were found. Vitamin D level was lower in CAD patients - Aa and aa genotype carriers (33,8±33,9 nmol/l ,p=0,02 and 24,7±4,9 nmol/l, p=0,05 respectively in comparison to vitamin D level = 43,3 ±4,2 nmol/l in AA genotype carriers). Conclusion The bb genotype of Bsm-I VDR gene polymorphism is associated with an increased risk of CAD. A carriage of b allele in CAD patients is associated with lower level of vitamin D and HDL cholesterol. A carriage of a allele of Apa-I VDR gene polymorphism in CAD patients is associated with lower level of vitamin D and HDL cholesterol.
Keywords: coronary artery disease; vitamin D receptor; gene polymorphism; dyslipidemia; high density lipoproteins.